Ending life - Battin, Margaret Pabst (Oxford University Press, 2005)
Margaret Pabst Battin has established a reputation as one of the top philosophers working in bioethics today. This work is a sequel to Battin's 1994 volume The Least Worst Death. The last ten years have seen fast-moving developments in end-of-life issues, from the legalization of physician-assisted suicide in Oregon and the Netherlands, to a furor over proposed restrictions of scheduled drugs used for causing death, and the development of "NuTech" methods of assistance in dying. Battin's new collection covers a remarkably wide range of end-of-life topics, including suicide prevention, AIDS, suicide bombing, serpent-handling and other religious practices that pose a risk of death, genetic prognostication, suicide in old age, global justice and the "duty to die." It also examines suicide, physician-assisted suicide, and euthanasia in both American and international contexts